Experimental analysis of various configurations of metal sheets in the reinforcement of flexion of reinforced concrete beams - Deghenhard, C. C.; Teixeira, T.; Vargas, A.; Vito, M.; Piccinini, Â. C.; Do Vale Silva, B. (Revista ALCONPAT, 2016)
The external structural reinforcing steel, in the way of steel sheets attached with epoxy adhesive, is an option to increase the load capacity of reinforced concrete elements. This study evaluated concrete beams reinforced with steel sheets SAE 1020 of different thicknesses (0.75, 1.50, and 2.25 mm), longitudes (80 and 150 cm), and configurations (U-shape or flat) with the purpose of reviewing and comparing the best practices with sheets adhered to the structural reinforcement. Twenty-one beams were built with a cross-section of 12 x 20 cm and a longitude of 200 cm, with C25 concrete, and flexion frame with 2 Ø10 mm. The beams where subject to a four-point flexural test, which allowed analyzing the optimal loads and vertical displacements. Thus, a comparison relative to the performance of the beams is presented. Keywords: structural reinforcement; cast steel plates; reinforced concrete beams